Economic Foundations of International Law - Eric A. Posner, Alan O. Sykes (Harvard University Press, 2013)
Recent years have witnessed a torrent of new writing that uses concepts from economics to analyze international law. The economic or rational choice approach to public international law assumes that states are rational, self- interested agents that use international law in order to address international externalities and obtain the other benefi ts of international cooperation. This approach also emphasizes that because no external enforcement agent such as a world government exists, international law must be self- enforcing. States must believe that if they violate international law, other states will retaliate or in other ways respond negatively. This self- enforcement constraint is the major analytic distinction between international law and domestic law, where it is usually safe to assume that parties can rely on the government to enforce the law. Although the economic approach to international law is only about ten years old, a large literature has already accumulated.1 Many of the earliest works focused on the question of compliance, asking what reason rational states have for complying with international law. Since then, scholars have turned their attention to substantive areas of law— human rights, the law of the sea, the laws of war, environmental law, and so forth— and general themes such as the role of adjudication and of international organizations. The purpose of this book is to gather together and build on many of the ideas from this body of work and to present them in a manner suitable as an introduction for students and as a reference work for scholars. We mainly have in mind law students and law professors, but we hope that po liti cal scientists, economists, and other scholars who work in international relations will fi nd this book useful as well. Some background about the intellectual antecedents of this work will be helpful. Most scholars who write about international law take a doctrinal approach, in which they analyze legal sources for the purpose of determining what the law is. Where scholars ventured outside the doctrinal realm, they tended to be infl uenced by currents in legal philosophy and legal history. Most international law scholars ignored the revolution in (domestic) legal scholarship of the 1960s and 1970s, which introduced social science methods, and in par ticu lar economic methods, to legal scholarship. Only international trade scholars, in the spirit of their enterprise, imported economic ideas into their fi eld. Economic analysis of public international law began only in the 1990s and, after a slow start, accelerated in the early 2000s.